AB0880 Farber Disease Diagnosed as Juvenile Idiopathic Arthritis. (10th June 2014) - Sόlyom, A.; Karabul, N.; Simonaro, C.; Galanin, I.; Schuchman, E.
Abstract : Background: Farber lipogranulomatosis (Farber Disease; FD) is an ultra-rare lysosomal storage disorder resulting from the inherited deficiency of the enzyme acid ceramidase, and the accumulation of the lipid substrate ceramide. Ceramide is a pro-inflammatory and pro-apoptotic lipid that has been implicated in the pathogenesis of cartilage disorders 1 . Farber Disease has a heterogeneous presentation ranging from a severe phenotype with respiratory and CNS involvement and an average life expectancy of <2 years (Type 1), to a moderate phenotype which generally includes joint swelling, contractures and pain (Type 3). Awareness of FD in the pediatric rheumatology community is limited due to the rarity of the disease. The clinical similarity between the moderate Farber phenotype and the more severe forms of Juvenile Idiopathic Arthritis (JIA) suggests that moderate Farber Disease cases may be initially diagnosed as JIA. Objectives: To test the hypothesis that moderate Farber Disease has been diagnosed as Juvenile Idiopathic Arthritis in practice. Methods: We conducted a literature search of Farber Disease case studies since 1990. Moderate Farber Disease patients were defined as surviving into their third year of life without hepatosplenomegaly or significant neurologic involvement. Results: The literature search identified 84 unique papers with 35 comprising Farber Disease case studies. Of the overall case studies, 40% (n=14) described patients with moderate disease. 36% (n=5) of these patients were initially diagnosed as having JIA. Conclusions: A significant percentage of moderate Farber Disease patients are likely diagnosed as having JIA. Given this finding, it is important to increase awareness of Farber Disease in the pediatric rheumatology community. Differential diagnosis can be made by accounting for the comparatively early onset, progressive symmetric arthritis, presence of subcutaneous nodules at the joints, scalp and/or spine, and an unusual, hoarse cry or voice (due to nodule formation on the larynx) in FD patients. Based on experience with bone marrow transplantation in Farber Disease 2, enzyme replacement therapy could resolve or significantly attenuate the arthritis phenotype in patients. Such therapy is currently under development. We propose that Farber Disease can account for specific cases diagnosed as JIA, and that clinically guided genetic screening of the JIA population will reveal patients who can benefit from disease-specific care and treatment. References: Alayoubi AM, et al., Systemic ceramide accumulation leads to severe and varied pathological consequences. EMBO Mol Med. 2013, 5: 827-842. Ehlert K, et al., Farber disease: clinical presentation, pathogenesis and a new approach to treatment. Pediatr Rheumatol Online J. 2007, Jun 29; 5:15. Disclosure of Interest: A. Sόlyom Grant/research support: Plexcera Therapeutics LLC, N. Karabul Grant/research support: Plexcera Therapeutics LLC, C. Simonaro: None declared, I. Galanin Shareholder of: Plexcera Therapeutics LLC, E. Schuchman Shareholder of: Plexcera Therapeutics LLC DOI: 10.1136/annrheumdis-2014-eular.2532